Dye-sensitised semiconductors modified with molecular catalysts for light-driven H2 production. (19th November 2015) - Willkomm, Janina; Orchard, Katherine L.; Reynal, Anna; Pastor, Ernest; Durrant, James R.; Reisner, Erwin
Abstract : Recent progress and basic understanding in the emerging field of dye-sensitised photocatalysis for light-driven hydrogen production is reviewed. Abstract : The development of synthetic systems for the conversion of solar energy into chemical fuels is a research goal that continues to attract growing interest owing to its potential to provide renewable and storable energy in the form of a 'solar fuel'. Dye-sensitised photocatalysis (DSP) with molecular catalysts is a relatively new approach to convert sunlight into a fuel such as H2 and is based on the self-assembly of a molecular dye and electrocatalyst on a semiconductor nanoparticle. DSP systems combine advantages of both homogenous and heterogeneous photocatalysis, with the molecular components providing an excellent platform for tuning activity and understanding performance at defined catalytic sites, whereas the semiconductor bridge ensures favourable multi-electron transfer kinetics between the dye and the fuel-forming electrocatalyst. In this tutorial review, strategies and challenges for the assembly of functional molecular DSP systems and experimental techniques for their evaluation are explained. Current understanding of the factors governing electron transfer across inorganic-molecular interfaces is described and future directions and challenges for this field are outlined.